ANALISA SIFAT MEKANIS KOMPOSIT EPOKSI/ PARTIKEL SILIKA DARI EKSTRAKSI SEKAM PADI (Bagian I: Eksperimental) - Mulyadi, Mulyadi (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2019)
This work is focused on the effect of silica(silicon dioxide)on mechanical properties of modified epoxy resin. Eposchon A&B resin were utilised as a matrix to bind silica particles which were extracted from rice husk usingpyrolysis method. Eposchon A and Eposchon B were mixed with ratio 1:1. Silica with0, 2, 4 and 5% content by weight was introduced into Eposchon resin system. This composite mixtures were poured into silicon rhodorsil RTV mould to provide bending and fracture toughness coupon tests. The results revealed that bending strength of modified epoxy resin was improved by 14% for the maximum with 4% of silica content. On the other hand, fracture toughness were decreased as silica particles introduce into the epoxy system. Furthermore, fracture toughness enhanced as the content of silica higher up to 5%. It is concluded that silica from rice husk is potentials filler for polymer composite materials